Genetics of kidney development: pathogenesis of renal anomalies - Hyewon Hahn (Korean Pediatric Society, 2010)
Congenital anomalies of the kidney and urinary tract (CAKUT) account for more than 50% of abdominal masses found in neonates and involve about 0.5% of all pregnancies. CAKUT has a major role in renal failure, and increasing evidence suggests that certain abnormalities predispose to the development of hypertension and cardiovascular disease in adulthood. To understand the pathogenesis of human renal anomalies, understanding the development of kidney is important. Diverse anomalies of the kidney corresponding to defects at a particular stage of development have been documented recently; however, more research is required to understand the molecular networks underlying kidney development, and such an investigation will provide a clue to the therapeutic intervention for CAKUT.